Strategi Cyber Public Relations PT Gojek Indonesia - Argarini, Fitri; Andamisari, Dessy (Jurnal Mahardika Adiwidia, 2021)
This research is focused on the implementation of PT Gojek Indonesia's Cyber PR in supporting the company's image. The purpose of this study is to understand how the implementation of PT Gojek Indonesia's Cyber Public Relations in supporting the company's image and how to overcome competition with other online transportation companies. Cyber PR in its implementation involves the interaction of message dissemination (Cutlip et al.), namely 7C consists of, Credibility, Context, Content, Clarity, Continuity and consistency, Channel, Capability of the audience. In supporting the image, one of the factors needed is service (core service, facilitating service, supporting service). The paradigm in this study is post positivism. The method used is descriptive qualitative and data collection is done by interviewing key informants and non-key informants, observation, and literature study. The results of the study show that the implementation of Cyber Public Relations using online media has the advantage that it is more measurable (can be seen by followers), targeted and effective (accurately achieving goals). In supporting the company's image, Public Relations of PT Gojek Indonesia implements by utilizing internet technology through social media that is easily accessible to the public with innovative content aimed at getting a positive response so that Gojek is always remembered and close to the hearts of the public. 2. In overcoming competition, Public Relations PT Gojek Indonesia always innovates with support services or services that differentiate them from competitors.